Revisión exploratoria de la literatura sobre Staphylococcus aureus meticilino resistente en el área de la atención en salud. (2021)
The main causes of the acceleration, in the increase of bacterial resistance, are the improper and excessive use of antibiotics, the prevention and control of infections and the ability of microorganisms to evolve their resistance, through different mechanisms, such as plasmids, genes, and enzymes among others.